(untitled) (CIPEEX, 2025)
Cystic fibrosis (CF) is a chronic, autosomal, multisystem disease that reduces life expectancy and has a high mortality rate in children. Physical exercise specifically improves the digestive and respiratory systems, thus contributing to a better quality of life (QoL) in CF patients. The objective of this study was to determine whether aerobic or resistance exercise improves the QoL of CF patients. This is an integrative review based on randomized controlled clinical trials. The search was conducted between January and February 2025 in the PubMed, BVS, and SciELO databases, including articles from the last 10 years, in English, that evaluated the QoL of CF patients. Of the 29 studies found, 4 met the inclusion criteria. The descriptors used were Cystic fibrosis OR Mucoviscidosis AND Exercise AND Quality of life. The methodological quality of the studies was assessed using the Physiotherapy Evidence Database (PEDro). The results showed that two of the four trials reported QOL benefits from aerobic and resistance exercise. We conclude that regular, supervised exercise contributes to better QOL in CF patients, and it is essential that healthcare professionals be prepared to provide appropriate guidance to these individuals.